Liver stiffness in chronic hepatitis C virus infection - Mihăilă Romeo-Gabriel (Sciendo, 2019)
Introduction. The severity of liver fibrosis can be assessed noninvasively today by liver stiffness measurements. Vibration-controlled transient elastography, shear wave elastography or magnetic resonance elastography are techniques increasingly used for this purpose.